2010
DOI: 10.1177/0964663910369054
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Disciplinary Definitions and Understandings of ‘Paedophilia’

Abstract: Despite the current high-profile concern over paedophiles and paedophilic activity, there is no easily accessible or widely accepted multi-disciplinary definition of paedophilia. Commentators have pointed to a general contemporary misunderstanding surrounding the subject of paedophilia, and to the tensions between strong beliefs and facts in both societal and correctional contexts. We suggest that the current situation — societal, clinical and legal — can be problematic for both offenders and practitioners who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 16 publications
0
24
0
Order By: Relevance
“…Harper and Hogue (2014) found that a large proportion of British media reports about sexual crime focus on offenses perpetrated against children. Additionally, it has been reported that sexual offenders against children are homogeneously labeled as 'pedophiles' (Feelgood & Hoyer, 2008;Harper & Hogue, 2015b;Harrison, Manning, & McCartan, 2010;Silverman & Wilson, 2002). Recent research has shown that the impact of the 'pedophile' label on judgments (e.g., about sentencing) can be profound.…”
Section: The Influence Of Labels On Attitudes and Perceptions About Smentioning
confidence: 99%
“…Harper and Hogue (2014) found that a large proportion of British media reports about sexual crime focus on offenses perpetrated against children. Additionally, it has been reported that sexual offenders against children are homogeneously labeled as 'pedophiles' (Feelgood & Hoyer, 2008;Harper & Hogue, 2015b;Harrison, Manning, & McCartan, 2010;Silverman & Wilson, 2002). Recent research has shown that the impact of the 'pedophile' label on judgments (e.g., about sentencing) can be profound.…”
Section: The Influence Of Labels On Attitudes and Perceptions About Smentioning
confidence: 99%
“…In terms of their social interactions, Child Sexual Abusers (CSA), including paedophiles, are often quite adaptive knowing when to pursue, stop and alter their sexual offending behaviours; this is why many of them can have multiple victims, with the abuse often carrying on for years without being discovered by a third person/party. Although, CSA tend to be viewed heterogeneously rather than homogenously with explanations seeming to focus on its assumed homogeneous characteristics, instead of or in spite of its recognised heterogeneous nature (Bickley & Beech, 2001;Harrison et al, 2010). This is problematic as not all forms of child sexual abuse are similar, with different offender typologies (CSA, paedophile, incest abuser, etc.)…”
Section: Introductionmentioning
confidence: 92%
“…Many of the challenges of defining the scope of sexual violence are linked to the fundamental question about how to consistently define sexual violence (Harrison et al, 2010). Estimates of sexual violence will vary widely depending upon how broadly or narrowly the term is defined (Zeuthen & Hagelskjaer, 2013); especially as there is a broad range of legal and clinical categories of sexual violence, both nationally and internationally.…”
Section: Sexual Violence: Definitions and Understandingsmentioning
confidence: 99%
“…Another example of conflagration of definitions is between child sexual abuse and pedophilia. The two terms are often used interchangeably in society (McCartan, 2010); when in fact we are talking about two distinct populations (Harrison et al, 2010), one that is primarily based on breaking social norms as well as laws (child sexual abuse) and the other primarily viewed as being a clinical issue (paedophilia). Someone who commits a child sexual offense can be a pedophilic or a hebophilic but does not have to be and a pedophile does have to commit a contact offence to be labelled as such.…”
Section: Sexual Violence: Definitions and Understandingsmentioning
confidence: 99%